Dampak implementasi Sistem Perbendaharaan dan Anggaran Negara terhadap kinerja pegawai: pengujian model unified theory of acceptance and use of technology generasi ketiga - Martinus Hanung Setyawan; Levana Dhia Prawati (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2022)
The State Treasury and Budget System (SPAN) is one of digital electronic government (e-government) platforms which is implemented massively by the Government of the Republic of Indonesia as part of the development of the Integrated Financial Management Information System (IFMIS). Some studies to measure the acceptance and success model of the system implementation are mostly only focusing on user behavior parameters of information systems. These studies have not addressed the performance parameters. Within the eight-year implementation of SPAN, only few researchers conducted empirical studies to prove its impact on employee performance. The Unified Theory of Acceptance and Use of Technology (UTAUT) 3’rd Generation model is the next model for measuring the information system acceptance and success that links to various endogenous job performance variables. The model compares the increasing ability to use technology features (feature-level use), which results in the concept of transformational leadership to achieve performance. This study aims to prove the success of SPAN implementation using the UTAUT 3’rd Generation model which has been modified. The sampling method in this study used a survey with a questionnaire tool. The samples that were successfully obtained from 171 respondents who are officers in the Head Office of the Directorate General of Treasury, Regional Office of the Directorate General of Treasury, and KPPN throughout Indonesia. Hypothesis was tested with the Outer and Inner models Structural Equation Modelling (SEM) Partial Least Squares (PLS). The results of this study indicates that the variable feature-level use is proven to intervene the positive influence of facilitating conditions and behavioral intentions on job performance. The variable of habit has no effect on the feature-level use. The transformational leadership also has no moderate impact on habits and the feature-level use.